MNEs' agency within institutional contexts : a study of Walmart's post-acquisition practices in Mexico, Germany, and Japan - Tsui-Auch, Lai Si (2021)
The issue of MNEs' adaptation to host country institutional environments in their post-cross-border acquisition implementation, and the outcomes thereof, remains underexplored in international management studies. The purpose of this paper is to assess the applicability of three institutional approaches — (1) the earlier variant of the neoinstitutional theory (ENIT), (2) its recent variant (RNIT), and the comparative institutional analysis approach (CIA) — to explain (non)adaptation behavior in host country environments. Using Walmart's acquisition cases, we show that the MNE adopted a non-adaptation behavior in Mexico and Germany—countries which represent vastly different institutional environments—and succeeded in the former, but failed and withdrew from the market in the latter. However, in the Japanese institutional environment, which is similar to the German one, Walmart engaged in selective adaptation and survived in the market. Based on the case data, we offer a critical assessment of the applicability of the three approaches. These three approaches provide a base on which to develop a model to explain the relationship between institutional influences, an MNE's organizational agency and adaptation behavior, as well as outcomes. Moreover, we discuss future research directions and provide implications for practitioners related to MNEs' adaptation behavior and the ensuing outcomes in host markets.